Wacana Poskolonial: Islamic Worldview Dalam Studi Hubungan Internasionsl Kontemporer - Muhammad Nidhal Ezzat Luthfi (Program Studi Hubungan Internasional FISIP Universitas Jayabaya, 2022)
Modern International Relations thoughts are forms of colonialization of Western discourse on the non-Western ontology of reality, epistemology and axiology. Therefore the study of IR needs to represent small narratives, especially from the post-colonial discourse. Post-Cold War, the global revival phenomenon of religious discourse became a new agenda on IR discipline. The emergence of the Islamic tradition thought which places Islam as the most important basis on its scientific development opposes the mainstream tradition of IR positivistic. Islam with its unique Islamic worldview has a comprehensive dimension which also includes basic principles on exercising relations between nations. This article seeks to revive the Islamic perspective in contemporary IR studies to celebrate the plurality of thinking beyond the secular Western IR tradition. However, it is still difficult to develop a systematic and structured understanding of Islamic IR theorization as codified in the positivist and post-positivist paradigms